2016
DOI: 10.1088/0964-1726/25/10/105002
|View full text |Cite
|
Sign up to set email alerts
|

Modeling and experimental verification of frequency-, amplitude-, and magneto-dependent viscoelasticity of magnetorheological elastomers

Abstract: Magnetorheological elastomers (MREs), a smart composite, exhibit dual characteristics of both MR materials and particle reinforced composites, i.e., the viscoelasticity of MREs depends on external magnetic field as well as strain amplitude and excitation frequency. In this article, the principle of a frequency-, amplitude-, and magneto-dependent linear dynamic viscoelastic model for isotropic MREs is proposed and investigated. The viscoelasticity of MREs is divided into frequency-and amplitude-dependent mechan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 44 publications
1
12
0
Order By: Relevance
“…In this experimental study, we check the above hypothesis by examining for the first time the dynamic compression properties of isotropic/anisotropic composite silicon MREs in parallel and series configurations ( Figure 1) under a dynamic compressive strain with varying amplitude (from 0.25% to 1.5%) at zero and at 0.5T magnetic field. Only the magnetic field-strain amplitude coupling effect was considered in this study since the excitation frequency does not influence the MR effect [17], [18].…”
Section: Introductionmentioning
confidence: 99%
“…In this experimental study, we check the above hypothesis by examining for the first time the dynamic compression properties of isotropic/anisotropic composite silicon MREs in parallel and series configurations ( Figure 1) under a dynamic compressive strain with varying amplitude (from 0.25% to 1.5%) at zero and at 0.5T magnetic field. Only the magnetic field-strain amplitude coupling effect was considered in this study since the excitation frequency does not influence the MR effect [17], [18].…”
Section: Introductionmentioning
confidence: 99%
“…[236,257,258] The components involved in this combination can be modified to yield other possibilities. [235,251,[259][260][261] For example, the development of a higher-order fractional derivative model can be achieved by combining a fractional Maxwell model with a fractional Kelvin model in parallel where it leads to seven material parameters. [235] It is noted that the fractional Maxwell model was found to be more diverse in describing both MREs' shear storage and shear loss moduli compared with the two-Maxwell model which comprised two-integer-order Maxwell chains.…”
Section: Five Parameters Are Involvedmentioning
confidence: 99%
“…Besides, increasing strain amplitude can result in material softening by destroying the magnetic particle network arrangement. Considering the Payne effect for isotropic MREs, Xin et al [ 251 ] used the Kraus model [ 252 ] and magnetoelastic framework, to develop a viscoelastic model that takes mechanical and magnetic viscoelastic properties into account. The results indicated that in pure mechanical loading, the Kraus model is able to predict mechanical viscoelasticity with acceptable accuracy where both the shear storage and loss moduli increase with increasing excitation frequency.…”
Section: Modeling Of Mresmentioning
confidence: 99%
“…The most challenging attaches with dynamic behaviors of MR materials is accurately describing the highly nonlinear hysteresis response by the simple model. Bai et al [ 22 ] first proposed the principle of a multi‐variable‐dependent, i.e. frequency, amplitude, and magnetic field, the linear dynamic viscoelastic model for isotropic MR elastomer.…”
Section: Introductionmentioning
confidence: 99%